Strategi Pembelajaran Guru Bahasa Indonesia dalam Meningkatkan Kemampuan Menulis Cerita Siswa Kelas IV MI Nurul Islam Jakarta - Noviyanti Nurdiniah; Ahmad Farid; Abudzar Al-Ghifari (PT PUSTAKA CENDEKIA GROUP, 2025)
Indonesian is both the national language and the first language used by all citizens of Indonesia. Therefore, it is important for Indonesian children to master the Indonesian language from an early age. Indonesian language learning begins with listening and speaking skills, and then progresses to constructing correct sentences. As children grow older, the difficulty in understanding words and sentence structures increases. This study aims to examine the Indonesian language teaching strategies to improve storytelling writing skills among fourth-grade students at MI Nurul Islam Jakarta. The approach used in this study is descriptive qualitative, with informants consisting of the Indonesian language teacher, class teacher, and students. Data collection techniques employed include observation, interviews, and documentation, with triangulation used to ensure the validity of the information. The results show that the teaching strategies applied by the Indonesian language teacher have been effective in improving students' storytelling writing skills. However, the biggest challenge faced was the lack of material students received in the previous grade, which made it difficult for them to develop story ideas. A supporting factor found was the connection between the material taught in grade 3 and grade 4, which helped the teacher deliver the material in a continuous manner. These findings contribute to the understanding of the importance of curriculum continuity between grade levels and the use of more varied strategies in teaching writing. This study suggests the need for increased use of more creative teaching media and attention to students' foundational readiness in following lessons.